THE IMPACT OF SERVICE QUALITY, PRICE, AND PROMOTION ON CUSTOMER SATISFACTION AT MIROTA KAMPUS YOGYAKARTA - Saptomo, Chrisentianus Abdi; Pomantow, Charen; Kaloeti, Ade Kristianus (Manager : Jurnal Ilmu Manajemen, 2024)
The aim of this study is to analyze the significance of the influence of service quality, price, and promotion on customer satisfaction. This research is a quantitative study using secondary data and primary data obtained from questionnaires that have been filled out. The population in this study is all customers who have shopped at Mirota Kampus. Sampling was done using purposive sampling method and obtained 100 respondent samples for the study. The analysis tools used are multiple linear regression and f-test. Based on the analysis results, it shows that service quality, price, and promotion partially have a significant influence on customer satisfaction. Furthermore, the variables of service quality, price, and promotion simultaneously have a significant influence on customer satisfaction.